THE RELATIONSHIP BETWEEN THE PARITY AND THE OCCURRENCES OF LOW BIRTH WEIGHT (LBW) - MUHYIDDIN, HUSNUL AMALIAH (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2024)
The Infant Mortality Rate (IMR) is a key indicator for assessing infant health, reflecting the current state of child health. According to WHO, most IMRs (60-80%) are caused by low birth weight babies weighing less than 2500 grams. LBW infants have a higher risk of morbidity and mortality compared to normal birth weight infants. This study aims to understand the relationship between parity and the incidence of LBW in UPT RSUD Lamaddukkelleng, Wajo Regency. The research method used was analytic observational with a case control approach. The sample consisted of mothers who gave birth to LBW babies as cases and mothers who gave birth to normal birth weight babies as controls. Data were collected from medical records of Lamaddukkelleng Hospital and analyzed using Chi-Square test. The results showed a significant relationship between parity and the incidence of LBW in UPT RSUD Lamaddukkelleng Wajo Regency, with a p value = 0.000 < 0.05, thus rejecting the null hypothesis (H0).